Disrupting terrorist activity: What are the limits to criminal methods of disruption? - Stuart Macdonald (Beyond Human Rights and the War on Terror, 2018)
In furtherance of its commitment to prosecuting suspected terrorists, the UK has enacted a large number of terrorism precursor offences. In this chapter we evaluate this use of the criminal sanction and suggest that there is a need for greater legislative restraint. We develop this argument by first examining three non-criminal methods of disrupting terrorist activity: Terrorism Prevention and Investigation Measures (TPIMs); asset-freezing; and, proscription. Whilst each of these powers has been found to be necessary, we outline four sets of concerns about them that explain why they are regarded as less desirable in principle than prosecution. We then turn to terrorism precursor offences and, whilst agreeing that they are needed for the sake of prevention, argue that the wide range of such offences currently in force in the UK go too far in pursuit of this objective. As a result, the same concerns that apply to the non-criminal methods of disruption apply also to terrorism precursor offences. We argue that this is counter-productive, for it risks undermining the very features of the criminal law that give it its unique moral authority and legitimacy in the first place.